(untitled) (Psychology Travelogs, 2024)
A theoretical analysis of the psychological features of the development of stress resistance of socionomic professionals in the scientific psychological literature is carried out in the article. The stress resistance is an important component of the mental health of socionomic specialists and is a personality trait that ensures harmonious interaction between all components of mental activity in a stressful situation were determined. The psychological factors that contribute to the development of stress resistance of socionomic specialists have been determined, such as: individual psychological characteristics of the personality (high level of emotional stability, volitional self-regulation, activity, confidence in oneself and one’s actions); availability of functional capabilities of the central nervous system and neuromuscular apparatus; experience of solving stressful problems in the past and a positive forecast for the future; positive attitude and positive emotional background in stressful situations; the ability to adequately assess oneself in a stressful situation; support and approval from the social environment and psychological factors that negatively affect the development of stress resistance of socionomic specialists, such as: individual psychological characteristics of the individual (low level of emotional stability, balance, self-regulation, high level of anxiety; low level of adaptive capabilities of the individual organism; low level of the emotional and cognitive sphere (negative perception of information, negative forecast of a stressful situation). Based on the results of the study, the authors the psychological recommendations were developed, which will allow socionomic specialists to optimally adapt to stress situations and will provide the ability for self-regulation in professional activities.